Diurnal and Seasonal Variations in the Photosynthetic Characteristics and the Gas Exchange Simulations of Two Rice Cultivars Grown at Ambient and Elevated CO2 - Miao, Yuxuan; Cai, Yao; Wu, Hao; Wang, Dan (Frontiers in Plant Science, 2021)
Investigating the diurnal and seasonal variations of plant photosynthetic performance under future atmospheric CO2 conditions is essential for understanding plants adapting strategy to global change and valuable for estimating plant physiological characters using mechanic models. In this study, diurnal changes of net photosynthetic rate (Anet), stomatal conductance (gs) and photochemical efficiency of PSII (Fv′/Fm′) were measured in two rice cultivars grown in the open-top-chambers at ambient ( 450 μmol mol-1) and elevated ( 650 μmol mol-1) CO2 concentration ([CO2]) throughout the growing season for two years. The results showed that elevated [CO2] greatly increased Anet, especially at jointing stage. This stimulation was acclimated with the advance of growing season and was not affected by either stomatal limitations or Rubisco activity. Model parameters in photosynthesis model (Vcmax, Jmax and Rd) and two stomatal conductance models (m and g1) varied across growing stages and m and g1 also varied across [CO2] treatments and cultivars, which led to more accurate photosynthesis and stomatal conductance simulations when using these cultivar-, CO2- and stage- specific parameters. The results in the study suggested that further research is still needed to investigate the dominant factors contributing to the acclimation of photosynthetic capacity under future elevated CO2 conditions. The study also highlighted the need of investigating the impact of other environmental, such as nitrogen and O3, and non-environmental factors, such as additional rice cultivars, on the variations of these parameters in photosynthesis and stomatal conductance models and their further impacts on simulations in large scale carbon and water cycles.